Impact of Leadership Styles on Job Satisfaction and Employee Motivation: A Case Study of Private Banking Sector in Eastern Zone Afghanistan: https://doi.org/10.5281/zenodo.16935922 - Hayat Ullah; Naqib Ullah Jabarkhil (`, 2025)
This study examines the Impact of Leadership Styles on Job Satisfaction and Employee motivation. In this research the private banking sector of eastern zone of Afghanistan was studied. In the bank researcher check the satisfaction level of the employees and how leaders motivate their employees. A sample of 200 employees was taken from eastern private banks. this research shows the executive level leadership that how they treat the employees or subordinates. The five level Likert scale questionnaire was distributed in different branches to the respondent. In the questionnaire out of 200, 200 questions were received from respondents, regression and correlation was used to check the impact of different leadership styles. result shows that there is a significant positive impact on job satisfaction to Transformational leadership, Transactional leadership and Laissez faire leadership. The second variable result shows that there is significant positive impact between Employee motivation to Transformational leadership, Transactional leadership and laissez faire leadership. Keywords, Leadership Styles, Job Satisfaction, Employee Motivation, Transformational leadership